The benefit of abdominal sonography and chest X-ray for staging oral squamous cell carcinomas in stages UICC I and II. Issue 2 (February 2016) - Precht, Clarissa; Baustian, Sara; Tribius, Silke; Schöllchen, Maximilian; Hanken, Henning; Smeets, Ralf; Heiland, Max; Gröbe, Alexander
Abstract: Purpose: The purpose of this study was to evaluate how often distant metastases occur in localized oral squamous cell carcinomas (OSCC). The investigators hypothesize that abdominal sonography and chest X-ray may not be necessary for initial staging of early oral squamous cell carcinoma in UICC stage I/II. Material and methods: The investigators implemented a retrospective study. The study collective was composed of 124 patients with OSCC, who were treated in the department of oral and maxillofacial surgery during the years 2011–2015 at the University Medical Center Hamburg Eppendorf, Germany. We focused on age, gender, date of diagnosis, tumour stage (clinical and pathological), HPV status, occurrence of metastases, recurrences, date and frequency of staging and restaging (abdominal sonography, chest X-ray, CT Abdomen/Thorax, PET CT), follow up time and date of death. Descriptive and bivariate statistics were computed (chi-square test) and the P value was set at .05. Results: 19 distant metastases were found in 13 out of 124 patients (10.48%). Of those 20 metastases 5 were found in the liver (26.32%), 11 in the lung (57.89%) and 4 in the bone (15.79%). Hepatic metastases co-occurred in every case with pulmonary metastases. In one case bone metastases occurred without the presence of pulmonary metastases. There was no significant correlation of metastasis rate to T stage. But distant metastases were solely found in node positive patients. This was significant for pulmonary metastases, not for liver metastases. Only one out of 11 pulmonary metastases was diagnosed by chest X-ray. Conclusion: Abdominal sonography and chest X-ray can be omitted as a standard procedure in staging of localized node negative oral squamous cell carcinoma. A thoracic CT including the liver should be performed in patients with suspected lymph nodes metastases in the neck on CT. A skeletal scintigraphy or alternatively a PET/PET-CT should be added if there are signs and symptoms suspicious for bone metastases.